2022
DOI: 10.2298/pif2202063p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response as biomarker of exposure of a freshwater invertebrate model organism (Unio mancus Lamarck, 1819) to antifouling copper pyrithione

Abstract: Sublethal effects of copper pyrithione (CuPT) on an invertebrate model organism, freshwater mussel (Unio mancus), were assessed using oxidative stress parameters and histopathology. The environmentally relevant concentration of 5 ?g/l copper pyrithione was applied as a 96 h semi-static exposure. MDA levels in digestive gland (DG) significantly increased, compared to a control group (p < 0.001). Gill MDA levels also increased, but not significantly (p > 0.05). GSH level in DG increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In this study, the digestive gland was the most involved tissue in the modulation of the total glutathione levels. Recent data showed that GSH levels increased significantly in the digestive glands of freshwater mussel ( Unio mancus ) exposed to antifouling copper pyrithione, while thiol levels were unchanged in the gills [ 67 ]. These findings are in agreement with previous research in which the key role of the digestive gland in metal bioaccumulation and detoxification was discussed [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the digestive gland was the most involved tissue in the modulation of the total glutathione levels. Recent data showed that GSH levels increased significantly in the digestive glands of freshwater mussel ( Unio mancus ) exposed to antifouling copper pyrithione, while thiol levels were unchanged in the gills [ 67 ]. These findings are in agreement with previous research in which the key role of the digestive gland in metal bioaccumulation and detoxification was discussed [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study demonstrated that the hepatopancreas of crayfish suffered substantial structural damage as a result of accumulating distribution levels. Non-essential elements have been shown in other investigations [ 26 , 48 ] to accumulate in crayfish tissues as environmental concentration and exposure time increase.…”
Section: Discussionmentioning
confidence: 85%
“…Also, our results came along with results of Wang et al [ 25 ], who recorded a significant increase in SOD and GST activity after exposure of freshwater crab Sinopotamon henanense ’s gills to Cd. Furthermore, an increase in SOD level in both gills and hepatopancreas of Unio macus was noticed after exposure to Cu [ 26 ]. The studies indicated that gill and hepatopancreas tissues are the most sensitive tissues exposed to toxicants.…”
Section: Discussionmentioning
confidence: 99%